A systems perspective on data and analytics for distance education. Issue 2 (3rd April 2022) - Ifenthaler, Dirk
Abstract: This commentary provides a systemic perspective on data and analytics for supporting distance education environments. Distance education describes learning opportunities of geographically separated humans. With the advent of data and analytics in distance education, multiple benefits from data and analytics for distance education may be achieved. Three fields of interest for distance education linked to data and analytics will be examined: learning analytics design, educational data literacy, and change management. However, open questions concerning data and analytics for distance education remain, which shall be further investigated in future research initiatives.